Results of modified sinustrabeсulotomy in patients with primary openangle glaucoma - M. M. Bikbov; A. Je. Babushkin; O. I. Orenburkina (Oftalʹmologiâ, 2016)
Purpose: To study the short- and long-term results of modified sinus trabeculotomy (STT) in primary open-angle glaucoma (POAG).Patients and methods: We observed 42 patients (47 eyes) with POAG at 1‑3 stages aged 47‑85 (average age — 67.5 years). There were 27 women (64,3 %) and 15 men (35,7 %). The I stage of glaucoma was diagnosed in 17.0 % (8 eyes), II stage — in 44.7 % (21 eyes) and III stage in 38.3 % (18 eyes) patients. The average level of intraocular pressure (IOP) at the drug therapy was 29.2±1.5 mmHg (results obtained by pneumotonometer). All patients underwent a routine ophthalmic examination before and after surgery. Long-term results for period of 6‑24 months (13.1 months average) were assessed in 39 patients (43 eyes).Results. The most common early complications were hyphema (10.6 % patients) and ciliochoroidal detachment (6.4 % patents). Long-term results showed normalization of IOP in 93.0 % cases including 7.0 % against the background of additional therapy. Visual acuity preserved in 88.4 % cases, its reduction was observed in 11.6 % and was associated with the progression of glaucoma (7.0 %) and lens opacity (4.6 %). The field of view remained at the preoperative level in 90.7 % patients and narrowed in 9.3 %, mainly due to the progression of glaucoma process.Conclusion. Cruciate STT with anchoring of the scleral flap apex in suprauveal space in POAG in long-term results (up to 2 years) has a sufficiently high and sustained hypotensive effect (93.0 %), cataractogenic effect (4.6 %) and a relatively small number of complications (especially in case of ciliochoroidal detachment — just 6.4 %). We suggest this surgery in I‑III stages of POAG when the degree of expected postoperative scarring is small.